IMPACT OF THE AVAILABILITY OF NATURAL RESOURCES ON COUNTRIES’ ECONOMIC GROWTH - ANASTASIA ALEKSEEVNA Shalaeva (Мир новой экономики, 2018)
The article answers analyses the influence of different institutions on the country’s economic growth with large deposits of natural resources. This study points out the paradox faced by the researchers at the end of the last century: countries rich with natural resources demonstrate relatively lower rate of economic growth rather than their neighbors.The study answers the question: do natural resources have negative impact on economic growth of the country? And which factors also need to be analyzed? To achieve this there is a number of objectives: analysis of existing approaches for understanding of resource dependence, study of different countries real examples, econometric model development and detailed description of practical experience and problems in relation to one of the selected countries.This research is based on econometric methods and statistical analysis.The analysis of empirical data answered the question whether the availability of resources is a real „curse”? The hypothesis of influence for various parameters was tested for Russia, and indicates the possibility of its applicability to the Russian.